NURSING CARE FOR ACUTE PAIN IN POST-OPERATION FRACTURES - Ilkafah, Ilkafah; Lestari, Indah Dwi (Universitas Airlangga, 2021)
Introduction: Fracture is a condition which will cause interference with mobilization and pain in patients. In a fracture patient, the patient will be surgically operated or operated on. Complaints that often arise in patients due to after surgery is pain. Pain is a major nursing problem in fractures. The purpose of this study was to carry out nursing care for patients with acute pain in patients with Sinusra Radius Fracture Post Surgery in Dr. Soegiri Lamongan. Methods: This research used qualitative research case study approach. The research subject used was one patient with a nursing problem that is Acute Pain in Post Sinusra Radius Fracture Surgery. This study used 1 patient as a participant on 26 September 2019 to 28 September 2019 in Bougenvil 1 room Dr. Soegiri Lamongan. Data collection uses assessment by interview, physical examination, supporting examination and supported by other documentation. Data analysis with this research was carried out while still paying attention to research ethics. Results: The results obtained are acute pain nursing problems, with priority nursing actions efforts to overcome decreased pain in patients. After doing care for three days, there are decrease in pain scale as evidenced by the pain scale on the third day, the client improved with the original scale of 5 to 3. Conclusion: The conclusion from the research conducted found that deep breathing relaxation technique is one of the effective non-pharmacological pain management methods to reduce pain. To overcome the postoperative incident Sinus Radius Fracture, patients should take medication regularly, and control health services.